Pest risk assessment of Leucinodes orbonalis for the European Union - EFSA Panel on Plant Health (PLH); Claude Bragard; Paula Baptista; Elisavet Chatzivassiliou; Francesco Di Serio; Paolo Gonthier; Josep Anton Jaques Miret; Annemarie Fejer Justesen; Alan MacLeod; Christer Sven Magnusson; Panagiotis Milonas; Juan A. Navas‐Cortes; et al. (EFSA Journal)
Abstract Following a request from the European Commission, the EFSA Panel on Plant Health performed a quantitative risk assessment of Leucinodes orbonalis (Lepidoptera: Crambidae), the eggplant fruit and shoot borer, for the EU. The assessment focused on potential pathways for entry, climatic conditions favouring establishment, spread and impact. Options for risk reduction are discussed but effectiveness was not quantified. L. orbonalis is a key pest of eggplant (aubergine/brinjal) in the Indian subcontinent and occurs throughout most of southern Asia with records mostly from India and Bangladesh. The main pathway of entry is fruit of solanaceous plants, primarily exotic varieties of eggplant, Solanum melongena and turkey berry, S. torvum. The trade in both commodities from Asia is small but nevertheless dwarfs the trade in other Solanum fruits from Asia (S. aethiopicum, S. anguivi, S. virginianum, S. aculeatissimum, S. undatum). Other Solanum fruits were therefore not further assessed as potential pathways. The trade in eggplant from Asia consists of special fruit types and caters mostly to niche markets in the EU, while most eggplant consumed in Europe is produced in southern European and northern African countries, where L. orbonalis does not occur. Using expert knowledge elicitation (EKE) and pathway modelling, the Panel estimated that approximately 3–670 infested fruit (90% certainty range, CR) of S. melongena or fruit bunches of S. torvum enter into regions of the EU that are suitable for L. orbonalis establishment each year. Based on CLIMEX modelling, and using two possible thresholds of ecoclimatic index (EI) to indicate uncertainty in establishment potential, climates favouring establishment occur mostly in southern Europe, where, based on human population, approximately 14% of the imported produce is distributed across NUTS2 regions where EI ≥ 30; or 23% of the produce is distributed where EI ≥ 15. Escape of adult moths occurs mostly from consumer waste. By analysing results of different scenarios for the proportion of S. melongena and S. torvum in the trade, and considering uncertainties in the climatic suitability of southern Europe, adult moth emergence in areas suitable for establishment is expected to vary between 84 individuals per year and one individual per 40 years (based on 90% CR in different scenarios). In the baseline scenario, 25% of the solanaceous fruit from Asia is S. torvum, 75% is S. melongena and EI ≥ 30 is required for establishment. After accounting for the chances of mating, host finding and establishment, the probability of a mated female establishing a founder population in the EU is less than 1 in 100,000 to about 1 event per 622 years (90% CR in baseline scenario). The waiting time until the first establishment is then 622 to more than 100,000 years (CR). If such a founder population were established, the moth is estimated to spread at a rate of 0.65–7.0 km per year after a lag phase of 5–92 years. The impact of the insect on the production of eggplant is estimated to be 0.67%–13% (CR) if growers take no specific action against the insect and 0.13%–1.9% if they do take targeted actions. Tomato (S. lycopersicum) and potato (S. tuberosum) are hosts of L. orbonalis, but the insect does not develop to maturity in tomato fruit, and it does not feed on potato tubers under field conditions; hence, damage to potato can only occur due to feeding on shoots. Tomato and potato are not preferred hosts; nevertheless, impact can occur if populations of L. orbonalis are high and preferred hosts are not available. The Panel did not assess this damage due to insufficient information.